Peningkatkan Mutu Madrasah Diniyah Berbasis Masyarakat di Desa Laju Kidul Singgahan Tuban - Ismawati Ismawati (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2018)
The existence of madrasah diniyah in Indonesia is the first form of madrasah in Indonesia, but until now it is still a marginal educational institution. Imagine, madrasah diniyah in Indonesia just get special recognition and attention from the government these days alone, provided that madarasah diniyah contains learning (curriculum) which is recommended by the government. This research was conducted with qualitative method of case study with the research location in the village of Laju Kidul Singgahan Tuban and the results obtained are: The views of the society at Madrasah Diniyah Al Hidayah The rate of Singgahan Singgahan Tuban is very good and the quality of Madrasah Diniyah Al Hidayah Laju Kidul Singgahan Tuban when viewed at the input level, the process and its output are also quite good. Then Community participation in quality improvement in madrasah diniyah this at least provide supervision in the form of criticism, suggestions and inputs in the determination of curriculum, selection of entry and improvement of human resources. All layers of society there want to send their children to madrasah diniyah because based on the awareness of the importance of religious education in this globalization. They also participate in any activities that are self-supporting.